A feast for crows eaudiobook - Martin, George R. R. (A Song of Ice and Fire, 2011)
THE BOOK BEHIND THE FOURTH SEASON OF GAME OF THRONES , AN ORIGINAL SERIES NOW ON HBO.   Here is the fourth book in the landmark series that has redefined imaginative fiction and become a modern masterpiece. A FEAST FOR CROWS   After centuries of bitter strife, the seven powers dividing the land have beaten one another into an uneasy truce. But it’s not long before the survivors, outlaws, renegades, and carrion eaters of the Seven Kingdoms gather. Now, as the human crows assemble over a banquet of ashes, daring new plots and dangerous new alliances are formed while surprising faces—some familiar, others only just appearing—emerge from an ominous twilight of past struggles and chaos to take up the challenges of the terrible times ahead. Nobles and commoners, soldiers and sorcerers, assassins and sages, are coming together to stake their fortunes . . . and their lives. For at a feast for crows, many are the guests—but only a few are the survivors.   A GAME OF THRONES • A CLASH OF KINGS • A STORM OF SWORDS • A FEAST FOR CROWS • A DANCE WITH DRAGONS